On audit of object-oriented software reverse engineering models using extended semantic dimensions. (1st January 2013) - Oladipo, Onaolapo Francisca
An effective software reverse engineering methodology must provide functionalities to generate knowledge about a system and visualise the knowledge for comprehension. Given the importance of methodologies to reverse engineering a software system, there is a need to rigorously carry out performance analysis on them based on relevant criteria. This work investigated some previous testing models with their numerous lists of criteria and discovered that these models were developed towards analysing methodologies specifically developed to reverse engineer applications written in old compilers because legacy codes were originally considered written in old languages and they operated at different levels of abstraction. This paper therefore, presented a model for the audit of methodologies developed to reverse engineer object-oriented (OO) software systems using the extended semantic dimensions of the recovered abstractions as informational and evaluational criteria. The work also went further to build a performance evaluation methodology based on these criteria.